2011
DOI: 10.1063/1.3592288
|View full text |Cite|
|
Sign up to set email alerts
|

In situ analysis of elemental depth distributions in thin films by combined evaluation of synchrotron x-ray fluorescence and diffraction

Abstract: In this work we present a method for the in situ analysis of elemental depth distributions in thin films using a combined evaluation of synchrotron x-ray fluorescence and energy-dispersive x-ray diffraction signals. We recorded diffraction and fluorescence signals simultaneously during the reactive annealing of thin films. By means of the observed diffraction signals, the time evolution of phases in the thin films during the annealing processes can be determined. We utilized this phase information to parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…3e) and then abruptly become steeper. Numerical model calculations revealed that this steepening of the Cu-Kα intensity can be explained by Cu 2 Se segregation at the lm surface with a constant growth rate, 19,34 which is consistent with recent observations by real-time ellipsometry. 35 The steepening is more pronounced in detector 2 than in detector 1, because detector 2 has a lower exit angle and hence a higher surface sensitivity than detector 1.…”
Section: Role Of Cu Saturationsupporting
confidence: 76%
“…3e) and then abruptly become steeper. Numerical model calculations revealed that this steepening of the Cu-Kα intensity can be explained by Cu 2 Se segregation at the lm surface with a constant growth rate, 19,34 which is consistent with recent observations by real-time ellipsometry. 35 The steepening is more pronounced in detector 2 than in detector 1, because detector 2 has a lower exit angle and hence a higher surface sensitivity than detector 1.…”
Section: Role Of Cu Saturationsupporting
confidence: 76%
“…Additionally, X-ray fluorescence (XRF) signalseven of heavy elementsare measured simultaneously to the Bragg reflexes. These XRF signals provide information about material adsorption and desorption as well as elemental distributions [15,16].…”
Section: Energy Dispersive X-ray Diffraction (Edxrd)mentioning
confidence: 99%
“…Since the number of fluorescence signals that are measured under one or more fixed angles is limited, the depth distributions have to be parameterized such that the number of parameters does not exceed the number of measured fluorescence signals. It can be demonstrated that a simple parameterization (where the knowledge of phase formation gained from the simultaneously measured Bragg reflexes are taken as additional constrains) can be used to obtain in-situ depth distributions by a quantitative analysis of the fluorescence signals [16]. Figure 13.12 presents a series of depth distributions during a CuInS 2 synthesis process.…”
Section: Energy Dispersive X-ray Diffraction (Edxrd)mentioning
confidence: 99%
“…the formation mechanism) using various diffraction methods, but there has been very limited research on the electronic structure of these materials. 20,[29][30][31] There is a lack of information on the composition and bonding of the NCs, including the Cu/In ratio as well as the use of MPP as a capping ligand for CIS. MPP removes the need for high temperature annealing necessary in the case of the insulating ligands typically involved in the synthesis of the NCs.…”
Section: Introductionmentioning
confidence: 99%